2020
DOI: 10.2147/opth.s259704
|View full text |Cite
|
Sign up to set email alerts
|

<p>Protecting the Ocular Surface in Cataract Surgery: The Efficacy of the Perioperative Use of a Hydroxypropyl Guar and Hyaluronic Acid Ophthalmic Solution</p>

Abstract: To evaluate the effects of a hydroxypropyl guar (HPG) and hyaluronic acid (HA) ophthalmic solution in terms of post-cataract surgery dry-eye disease (DED) prevention. Patients and Methods: In this retrospective study, the data of 419 patients not previously affected by DED, who had undergone unilateral cataract surgery in 17 Italian centers with different perioperative lubricating regimens, were retrospectively reviewed. Patients who had instilled HPG/HA solution 3 times/day in the preoperative week and for tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Nevertheless, the presence of DED and its risk factors should be investigated preoperatively to avoid postoperative complications [1], thereby optimizing the ocular surface before surgery. A previous study of eyes not affected by preoperative DED [8] showed that a hydroxypropyl guar and the hyaluronic acid ophthalmic solution was effective in reducing post-cataract surgery ocular discomfort and tear instability, with higher BUT and lower symptoms when also administered in the preoperative period. In another multicentric study, the use of a lubricating solution two weeks before cataract surgery, in eyes with either preoperative healthy ocular surface or mild DED [7], had a protective effect against postoperative DED.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Nevertheless, the presence of DED and its risk factors should be investigated preoperatively to avoid postoperative complications [1], thereby optimizing the ocular surface before surgery. A previous study of eyes not affected by preoperative DED [8] showed that a hydroxypropyl guar and the hyaluronic acid ophthalmic solution was effective in reducing post-cataract surgery ocular discomfort and tear instability, with higher BUT and lower symptoms when also administered in the preoperative period. In another multicentric study, the use of a lubricating solution two weeks before cataract surgery, in eyes with either preoperative healthy ocular surface or mild DED [7], had a protective effect against postoperative DED.…”
Section: Discussionmentioning
confidence: 97%
“…In order to prevent onset or worsening DED after cataract surgery, the presence of DED, and its risk factors, should be investigated preoperatively [1]; optimizing the ocular surface before surgery is not only crucial in at-risk patients but can also be useful for all phacoemulsification candidates [7,8]. Moreover, appropriate intraoperative management-i.e., reducing ocular surface exposure to topical anesthetics and mydriatics, 2 of 9 preservative-containing eye drops, to the light of the microscope and to the ultrasound [9]and tailored postoperative treatment can effectively improve the quality of life of each surgical patient [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HA can be used with triglycerides, phospholipids, vitamin B12, coenzyme Q10, hydroxypropyl guar, antibiotics, or steroids. HA used with above compound could increase tear film thickness [ 71 ], improve oxidative stress in the conjunctival epithelium of patients with dry eye [ 72 ], sustains ocular surface [ 73 , 74 ], and reduce DES symptoms [ 67 , 75 , 76 ]. Eye drops containing HA are effective DES pharmaceutical vehicles [ 77 ].…”
Section: Applications Of Ha In Ophthalmologymentioning
confidence: 99%
“…One study carried out by Favuzza et al evaluated the effect of a hydroxypropyl guar (HPG) and hyaluronic acid (HA) ophthalmic solution before and during phacoemulsification in terms of post-cataract surgery dry-eye disease (DED) prevention. Patients who had instilled HPG/HA solution three times/day in the preoperative week and for two postoperative months had lower SPEED (Standard Patient Evaluation of Eye Dryness) questionnaire scores and higher tear break-up time scores than the group which only instilled HPG/HA for two postoperative months [ 50 ]. Hovanesian et al determined the effect of topical cyclosporine 0.09% on ocular surface regularity for the patients who were diagnosed with DED before the cataract surgery.…”
Section: Discussionmentioning
confidence: 99%